2012
DOI: 10.1371/journal.pone.0050029
|View full text |Cite
|
Sign up to set email alerts
|

Laser Fusion of Mouse Embryonic Cells and Intra-Embryonic Fusion of Blastomeres without Affecting the Embryo Integrity

Abstract: Manipulation with early mammalian embryos is the one of the most important approach to study preimplantation development. Artificial cell fusion is a research tool for various biotechnological experiments. However, the existing methods have various disadvantages, first of them impossibility to fuse selected cells within multicellular structures like mammalian preimplantation embryos. In our experiments we have successfully used high repetition rate picosecond near infrared laser beam for fusion of pairs of ooc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Gas-vapor bubble formation is necessary but insufficient for the cell fusion. Fused embryo development studies [21][22][23] do not permit separation of the effect of laser impact by itself from the fusion effect. So, the study of not fused (morphologically equal to control) embryo development allows us to understand how the laser impact by itself affects embryo viability and quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gas-vapor bubble formation is necessary but insufficient for the cell fusion. Fused embryo development studies [21][22][23] do not permit separation of the effect of laser impact by itself from the fusion effect. So, the study of not fused (morphologically equal to control) embryo development allows us to understand how the laser impact by itself affects embryo viability and quality.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Moreover, only laser nanosurgery allows fusing of selected blastomeres into multicellular embryo (fusing 2 or 3 blastomeres in four-cell embryo) without affecting the whole embryo. 21 In addition to laser-induced intraembryonic blastomere fusion, the effect of femtosecond laser irradiation on embryo viability can be of great interest for science. It was demonstrated that fused embryo viability after pico-and femtosecondlaser treatment remains relatively high compared with control untreated group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be mentioned that the formation of a long-lasting vapor bubble (4-8 µm in diameter) in the irradiated area, creating a pore in both adjacent cell membranes, has been shown to be a prerequisite for successful blastomere fusion [34]. Apart from blastomere fusion, MII-stage oocyte fusion or fusion of oocyte and blastomere has also been demonstrated in [35,36]. For this purpose, the ZP was removed, and lectin was used for cell aggregation.…”
Section: Application Of Ultrashort Laser Pulses For Oocyte/blastomere Enucleation and Embryonic Cell Fusionmentioning
confidence: 99%